Development of a comprehensive performance-testing protocol for competitive surfers - Sheppard, J. M.; Nimphius, S.; Haff, G. G.; Tran, T. T.; Spiteri, T.; Brooks, H.; Slater, G.; Newton, R. U. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Appropriate and valid testing protocols for evaluating the physical performances of surfing athletes are not well refined. The purpose of this project was to develop, refine, and evaluate a testing protocol for use with elite surfers, including measures of anthropometry, strength and power, and endurance. Methods: After pilot testing and consultation with athletes, coaches, and sport scientists, a specific suite of tests was developed. Forty-four competitive junior surfers (16.2 ± 1.3 y, 166.3 ± 7.3 cm, 57.9 ± 8.5 kg) participated in this study involving a within-day repeated-measures analysis, using an elite junior group of 22 international competitors (EJG), to establish reliability of the measures. To reflect validity of the testing measures, a comparison of performance results was then undertaken between the EJG and an age-matched competitive junior group of 22 nationally competitive surfers (CJG). Results: Percent typical error of measurement (%TEM) for primary variables gained from the assessments ranged from 1.1% to 3.0%, with intraclass correlation coefficients ranging from .96 to .99. One-way analysis of variance revealed that the EJG had lower skinfolds (P = .005, d = 0.9) than the CJG, despite no difference in stature (P = .102) or body mass (P = .827). The EJG were faster in 15-m sprint-paddle velocity (P < .001, d = 1.3) and had higher lower-body isometric peak force (P = .04, d = 0.7) and superior endurance-paddling velocity (P = .008, d = 0.9). Conclusions: The relatively low %TEM of these tests in this population allows for high sensitivity to detect change. The results of this study suggest that competitively superior junior surfers are leaner and possess superior strength, paddling power, and paddling endurance.